2021
DOI: 10.3390/app11115297
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Landscape Dependent Changes in Arbuscular Mycorrhizal Fungal Community Structure

Abstract: The roots of most plants host diverse assemblages of arbuscular mycorrhizal fungi (AMF), which benefit the plant hosts in diverse ways. Even though we understand that such AMF assemblages are non-random, we do not fully appreciate whether and how environmental settings can make them more or less predictable in time and space. Here we present results from three controlled experiments, where we manipulated two environmental parameters, habitat connectance and habitat quality, to address the degree to which plant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Hyphal density was then estimated through light microscopy at 200fold magnification and was classified as AMF hyphae and We additionally assayed DNA from the roots of the plants. Results of the AMF community composition in the roots in the two experiments have been described in Veresoglou et al (2021). In that study, we observed that α-and β-diversity differed little across the micro-landscapes.…”
Section: Harvestmentioning
confidence: 55%
“…Hyphal density was then estimated through light microscopy at 200fold magnification and was classified as AMF hyphae and We additionally assayed DNA from the roots of the plants. Results of the AMF community composition in the roots in the two experiments have been described in Veresoglou et al (2021). In that study, we observed that α-and β-diversity differed little across the micro-landscapes.…”
Section: Harvestmentioning
confidence: 55%
“…In light of the above, this special issue was introduced with the aim of opening a vivid discussion on the following topics: This special issue represents a concise and strong scientific reaction to our questions posed, with three Regular Full Length Research Articles ( [1] cited by 1, viewed by 474; [2] cited by 1, viewed by 878, and [3] cited by 28, viewed by 2772), and two Review Articles ( [4] viewed by 911; and [5] cited by 3, viewed by 1038). Various topics related to our posed questions-in general or in particular-have been addressed.…”
Section: 'Hide and Seek Of Soil Microbes-who Is Where With Whom And W...mentioning
confidence: 99%
“…In the second paper, the authors S.D. Veresoglou, L. Grünfeld, and M. Mola, [2] address how soil spatial structures in plant mesocosms, i.e., habitat connectance and habitat quality, alter the predictability/stochasticity of the community composition of arbuscular mycorrhizal fungi (AMF). This is one of very few studies experimentally quantifying how micro-landscape structures increase the stochasticity of AMF communities.…”
Section: 'Hide and Seek Of Soil Microbes-who Is Where With Whom And W...mentioning
confidence: 99%